Electrophysiological and psychophysical studies in assessment of visual functions in patients with hereditary optic neuropathy - Sheremet, N L; Ronzina, I A; Andreeva, N A; Zhorzholadze, N V; Murakhovskaya, Yu K; Nevinitsyna, T A; Shmelkova, M S; Krylova, T D; Tsygankova, P G; Gerasimidi, E S; Lyamzaev, K G; Skulachev, M V; et al. (Vestnik oftal'mologii, 2022)
To study the capabilities of electrophysiological and psychophysical examination methods for assessment of the functional state of ganglion cells, retina and optic nerve in patients with hereditary optic neuropathy (HON). The study included 60 patients (118 eyes) with a genetically confirmed diagnosis of HON. All study patients underwent visual field test (VFT), spectral optical coherence tomography (OCT), flash and pattern visual evoked potentials (VEP) (Flash-VEP, FVEP; Pattern-VEP, PVEP), photopic electroretinography with photonegative response (PhNR) registration and the color vision test. In 24 patients (46 eyes), these parameters were assessed before the start of treatment and one year later. The treatment involved the mitochondria-targeted antioxidant SkQ1 - plastoquinonyl-decyl-triphenylphosphonium bromide (PDTP) in the form of eye drops. The main PVEP components for 1.0° and 0.3° were registered in 20% and in 14% of patient eyes with HON and high visual functions, respectively. After one year of PDTP use, a significant decrease in P100 peak latency was found only in the group with disease duration of ≤1.5 years as of the time of treatment start ( <0.05). Significant differences were observed in the PhNR amplitude ( <0.004) between patients of the main and the control groups, as well as in the PhNR amplitude between patients with visual acuity of ≤0.1 and ≥0.13 ( <0.01). Patients with high visual functions were found to have a correlation between the PhNR amplitude, GCC thickness and the global loss index (GLV). Along with VFT, OCT and color vision tests, electrophysiological studies are one of the main methods of examining patients with HON. After one year of PDTP use, there was a significant decrease in the FVEP P2 peak latency in the group with a disease duration of ≤1.5 years as of the time of treatment start. The PhNR amplitude in patients with high visual functions was found to correlate with structural changes in the ganglion cell layer and the retinal nerve fiber layer.